Agent-Based Simulation of Contribution Games - Szilagyi, Miklos N (Games Review, 2015)
Agent-based simulation was performed for various contribution games. The amount of contribution can be constant or variable and the first few contributions are less, more, or equally important than the last few. We found that the results strongly depend on the participating agents’ personalities. Two types of personalities were investigated: Pavlovian and greedy. Our simple formula (Equation 2) provides valuable information about the outcomes of N-person games for Pavlovian agents.